Pengaruh Promosi dan Kualitas Layanan terhadap Keputusan Nasabah Menggunakan Layanan BSI Mobile pada Bank Syariah Indonesia KC Surabaya Dipenogoro - Nurul Azizah Aunillah Devy; Khusnul Fikriyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Indonesia is making rapid technological advancement. The evolution of banking performance will be influenced by the role of technology in the financial world. Bank Syariah Indonesia is one of them, and it has produced a mobile bsi service innovation. The goal of this study is to see how promotion and service quality variables influence customer decisions to utilize bsi mobile services, either separately or together. The outcomes of data testing are collected using quantitative data in this study. A total of 92 users of the Bsi mobile service at Bank Syariah Indonesia KC Surabaya Diponegoro were included in the study. Multiple linear regression was employed as the approach method. The partial test findings demonstrate that the variables of promotion and service quality have a beneficial impact on customer decision-making. Simultaneous test findings reveal that promotion and service quality variables influence customer decisions to utilize bsi mobile services in a positive and significant way.